Effect of Diospyrus mespiliformis Hochst (Ebenaceae) Stem Bark Extract on Some Biochemical and Hematological Parameters in CCl4 Induced Oxidative Stress in Albino Mice - Sani M.B; Yakubu M.Y; Ibrahim M. N; Umar A.M; Abubakar U.F; Isiyaku A (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Diospyros mesopiliformis is a species of the family Ebenaceae. In Nigeria, the stem-bark mixture is utilized in ethno-medical practice to treat and manage a variety of illnesses. The objective of this work was to identify the bioactive compounds and assess the potential protective effectiveness of Diospyrus mespiliformis stem-bark extracts against CCl4 induced oxidative stress in albino mice. Fifty mice were split into five groups and given various treatments for 28 days. Olive oil and 1% tween 80 orally were administered intraperitoneally to the control group. After injecting CCl4 into other four groups to cause oxidative stress, two of the groups were treated with Diospyrus mespiliformis stem-bark extract at 200 and 400 mg/kg bwt, one group received silymarin treatment at a dosage of 100 mg/kg bwt. and the last group was not given any treatment. Biochemical and hematological markers, such as urea, creatinine, cholesterol, HDL, LDL, triglycerides, RBC, WBC, hemoglobin, PCV, and platelet levels, were assessed using blood samples. Using One-way ANOVA, the means of a these parameters were compared. Phytochemical screening led to the identification of alkaloid, flavonoid, saponins, steroids, tannins and cardiac glycosides. The findings of this investigation also indicate the administration of CCl4 raises blood urea and creatinine levels. The administration of the extract, however, counteracts the effects of CCl4 on creatinine and urea. Furthermore, the CCl4 treatment resulted in a notable alteration in the levels of CHOL and HDL. When comparing the group treated with CCl4 with the other treatment groups and the usual control, oral administration of Diospyros mespiliformis stem bark extract as well as revealed a significant difference in CHOL and HDL levels. Red blood cells (RBC), packed cell volume (PCV), white blood cells (WBC), and platelet counts (PLT) were found to be unchanged in response to CCl4 administration, however, hemoglobin levels were significantly reduced. The levels of Red blood cell, white blood cell, packed cell volume, and platelet count were not significantly affected following the oral administration of Diospyros mespiliformis stem bark extract but hemoglobin levels were significantly raised in response to the extract and silymarin treatments. As evidenced by the reversal of CCl4 impact on hemoglobin and renal parameters, the study showed that the plant extract had potential ameliorative efficacy.